Intestinal parasitic infections and associated risk factors: A cross-sectional study in Sunggal District, Deli Serdang - Sinaga, Janry Lewis Hasan Sarma; Siahaan, Lambok; Amelia, Rina (Jurnal Prima Medika Sains, 2024)
Intestinal protozoan infections have been reported worldwide with highly variable prevalence rates, particularly in tropical and subtropical regions. Despite this, limited research has been conducted on intestinal protozoan infections over the past decade, both in Indonesia and specifically in North Sumatra. Therefore, further investigation into the prevalence and risk factors of intestinal parasitic infections, especially protozoan infections, in areas surrounding Medan is warranted. This cross-sectional study assessed the association between risk factors and intestinal parasitic infections among 136 residents of Sunggal District, Deli Serdang, selected using consecutive sampling. Participants underwent interviews to evaluate risk factors using a checklist and provided fecal samples, as well as livestock samples if applicable. Data were analyzed using the Chi-square test and Fisher's exact test. Results revealed a significant association between age and Protozoa infection (p = 0.001), helminth infection (p = 0.0002), and overall parasitic infection (p = 0.0001). However, no significant associations were found for other variables. Furthermore, sanitation and hygiene levels were not significantly associated with parasitic infections (p > 0.05). These findings suggest that the risk factors assessed in this study were not significantly associated with intestinal protozoan infections. Nonetheless, the prevalence of both overall parasitic infections and protozoan infections remains high, with a spectrum ranging from asymptomatic to symptomatic cases. Further research is needed to elucidate the complex interplay of factors contributing to the persistence of these infections in the region.